Corylin accelerated wound healing through SIRT1 and PI3K/AKT signaling: a candidate remedy for chronic non-healing wounds - Xiu, Yanghui; Su, Yu; Gao, Lihua; Yuan, Hui; Xu, Sennan; Liu, Ying; Qiu, Yan; Liu, Zhen; Li, Yuhang (Frontiers in Pharmacology, 2023)
Chronic non-healing wound is a considerable clinical challenge and research into the discovery of novel pro-healing agents is underway as existing therapeutic approaches cannot sufficiently meet current needs. Herein, we showed that corylin, a main flavonoid extracted from Psoralea corylifolia L, reduced inflammatory responses, promoted collagen deposition, and accelerated the healing of full-thickness skin wounds in mice. Exploration of the underlying mechanisms showed that corylin activated the PI3K/ AKT signaling, leading to fibroblasts' migration, proliferation, and scratch healing. Corylin also activated SIRT1 signaling, enhanced the deacetylation and cytoplasmic translocation of NF-κB p65, and therefore reduced LPS-induced inflammatory responses in macrophages. Furthermore, inhibition of PI3K/ AKT and SIRT1 pathway with LY294002 and EX527 prevent the therapeutic potency of corylin against chronic wounds. These results suggested that corylin may be a candidate for the development of novel pro-healing agents